An examination of the effects of family, school, and community resilience on high school students’ resilience in China - Qi, Chunlin; Yang, Nanchang (Frontiers in Psychology, 2024)
Resilience significantly impacts the academic achievement, psychological health, and future opportunities of high school students. More studies need to be conducted regarding the present state and factors that affect resilience among high school students in China. The current research addresses this deficiency by evaluating and investigating the degrees of resilience and the connections among Chinese high school students in four domains: individual, family, school, and community. Additionally, it explores differences in resilience among high school students based on their genders, geographical areas, and grade levels. A total of 667 high school students, utilizing four resilience scales, participated in the study. Chinese high school students demonstrated low resilience, with family resilience being the highest and community resilience being the lowest. School, family, and community resilience boosts high school students' resilience. Hence, specific measures to bolster resilience should prioritize enhancing high school students' familial, educational, and communal settings. This study also indicated that female, urban, and lower-grade high school students are more resilient than male, rural, and higher-grade students. Therefore, it is imperative to prioritize cultivating resilience in male, rural, and high-grade high school students, as they are likely to encounter more significant difficulties and stressors in their academic and personal realms. This study broadened the extent of resilience research and contributed to advancing resilience techniques by investigating the correlation between individual, family, school, and community resilience among Chinese high school students.